Peran Mahasiswa Kampus Mengajar 2 Sebagai “Agent Of Change dan Social Control” - Yorri Didit Setyadi; Dwi Wulandari; Lutfi Dwi Lestari; Wa Ode Meliasari; Ifit Novita Sari (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
Students are the assets of a nation because students are a group of people trained in various fields of knowledge and skills. State Junior High School 2 Tanggulangin s one of the target schools selected by the author and Ministry of Education and Culture as the place for the Kampus Mengajar 2nd Generation as the student change agent of the education program created by us, among them the implementation of literacy learning activities and student numeration aimed at improving the understanding of literacy and student numeration. Social control is a tool to control himself or society. In this case, the society underneath is the entire State Junior High School 2 Tanggulangin and students as the main object of Kampus Mengajar 2nd Generation activities